ADAMTSL4‐associated isolated ectopia lentis: Further patients, novel mutations and a detailed phenotype description. (14th May 2015) - Neuhann, Teresa M.; Stegerer, Annette; Riess, Angelika; Blair, Edward; Martin, Thomas; Wieser, Stefanie; Kläs, Rüdiger; Bouman, Arjan; Kuechler, Alma; Rittinger, Olaf
<x xml:space="preserve">Abstract</x> ADAMTSL4 mutations seem to be the most common cause of isolated ectoplia lentis (EL) and thus are important concerning the differential diagnosis of connective tissue syndromes with EL as main feature. In this study, we describe an additional cohort of patients with apparently isolated EL. All underwent a detailed clinical exam with cardiac evaluation combined with ADAMTSL4 mutation analysis. Mutations were identified in 12/15 patients with EL. Besides the European founder mutation p. (Gln256Profs*38) we identified five further mutations not yet described in the literature: p. (Leu249Tyrfs*21), p. (Ala388Glyfs*8), p. (Arg746His), p. (Gly592Ser), and p. (Arg865His). Clinical evaluation showed common additional ocular features such as high myopia, but no major systemic findings. In particular: no dilatation of the aortic root was reported on. This report increases the total number of patients with ADAMTSL4 mutations reported on today and reviews in detail the clinical findings in all patients reported on to date demonstrate, that these patients have a mainly ocular phenotype. There are no consistent systemic findings. The differentiation between syndromic and isolated EL is crucial for the further surveillance, treatment, and counseling of these patients, especially in young children. © 2015 Wiley Periodicals, Inc.